2011
DOI: 10.1111/j.1365-2036.2011.04741.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-viral therapy in haemodialysed HCV patients: efficacy, tolerance and treatment strategy

Abstract: SUMMARY BackgroundIn end-stage renal disease (ESRD) patients, hepatitis C virus (HCV) eradication improves patient and graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Limited data exist about combination antiviral therapy (conventional or pegylated IFN plus ribavirin) in CKD stages 3–5 patients. Some information about the use of monotherapy with pegylated interferon in dialysis populations exists [8287], and the available data on combined therapy (conventional or pegylated IFN plus ribavirin) in the CKD population derive mostly from studies of patients on maintenance haemodialysis [8896]. There is limited information on the clearance of IFN in patients with CKD stages 3 and 4.…”
Section: Antiviral Treatment Of Hcv In Chronic Kidney Disease: Recmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data exist about combination antiviral therapy (conventional or pegylated IFN plus ribavirin) in CKD stages 3–5 patients. Some information about the use of monotherapy with pegylated interferon in dialysis populations exists [8287], and the available data on combined therapy (conventional or pegylated IFN plus ribavirin) in the CKD population derive mostly from studies of patients on maintenance haemodialysis [8896]. There is limited information on the clearance of IFN in patients with CKD stages 3 and 4.…”
Section: Antiviral Treatment Of Hcv In Chronic Kidney Disease: Recmentioning
confidence: 99%
“…Combination antiviral therapy (IFN plus ribavirin) has not been recommended in prior guidelines [98]. According to preliminary findings [8896], ribavirin should be used in patients on maintenance haemodialysis in a cautious and well-monitored setting. Ribavirin use, indeed, is limited by haemolytic anaemia that can be particularly dangerous in patients with chronic kidney disease, who often have anaemia as well as other comorbidities (e.g., cardiac ischemia) at baseline.…”
Section: Antiviral Treatment Of Hcv In Chronic Kidney Disease: Recmentioning
confidence: 99%
“…They reported lower ribavirin serum concentrations in the first month of therapy for 1000 mg receiving group which disappeared later. At the end of the study, a positive correlation was detected between the first month ribavirin serum concentration and SVR rates and a dose of 1400 mg/week ribavirin was offered as optimal for hemodialysis patients [5] .…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have indicated that EPO dose may be increased up to 90.000 IU/week in order to prevent ribavirin induced anemia [5] . Due to some cost and payment restrictions, (according to social insurance instructions) EPO could be described as 15.000 IU/week in the presented patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation